2006
DOI: 10.1103/physrevlett.97.097802
|View full text |Cite
|
Sign up to set email alerts
|

Vortex Flow in Freestanding Smectic Films Driven by Elastic Relaxation of thecDirector

Abstract: We report a simple experiment in freestanding smectic films in which elastic distortions of the c director drive macroscopic flow. The flow field is visualized with tracer particles. Measurements are compared to predictions of a model that employs the coupled dynamic equations for director and velocity fields. Relaxation dynamics depends on the topology of the film center: for defect-free target patterns, shear flow provides the dominating contribution to the c director dynamics. In presence of a central topol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…There have been several reports of target patterns with many rings in a thin film of SmC LC [16,17,18,19,20]. If we compare our results to those reports, the C-director of the SmC phase plays the role of the director of the nematic.…”
Section: Discussionsupporting
confidence: 63%
“…There have been several reports of target patterns with many rings in a thin film of SmC LC [16,17,18,19,20]. If we compare our results to those reports, the C-director of the SmC phase plays the role of the director of the nematic.…”
Section: Discussionsupporting
confidence: 63%
“…Since the first descriptions of smectic freely suspended films about 40 years ago [1,2], they have been a rich source of scientific discoveries. Manifold studies have been devoted to understanding the structure, fluctuations and phase transitions in these films [3][4][5][6], hydrodynamic phenomena, and director field structures [7][8][9][10][11][12] as well as spontaneous pattern formation [13][14][15]. The dynamics and spontaneous self-organization of inclusions such as islands (regions of excess smectic layers) and droplets have been investigated [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…It should be mentioned that such vortex like patterns have been observed in freely suspended films of both Nematic 5 and Smectic liquid crystals 6 8 . It is shown that the vortex patterns in such liquid crystal experiments can be well studied in the frame work of electro-convection based instability theory 9 .…”
Section: Introductionmentioning
confidence: 79%